Analisis Faktor Motivasi Membaca Teks Arab Bagi Mahasiswa Program Studi Pendidikan Bahasa Arab - M Rofi'i (Qismul Arab: Journal of Arabic Education, 2023)
Motivation has a very strong influence on the cognitive and affective aspects of reading. Motivation affects a person's thinking style. When a person is interested in the text he reads, his understanding will increase more than when reading a text he is not interested in. This study describes the factors influencing the motivation for Arabic Language Education at STAI Syaichona Moh. Cholil Bangkalan will read Arabic texts in the Qira'ah lesson. Data collection techniques are carried out through interviews, observation, and documentation using descriptive qualitative methods. The collected data was analyzed and validated by the triangulation method. The results showed that six factors influence students' motivation to read Arabic text: (1) Reading ability. (2) Individual interest or desire. (3) Reading needs. (4) Social support. (5) Technology and learning resources. and (6) Supportive conditions and facilities.